Multi-Package Delivery Optimization with Drone - Yilmazer, Merve; Karakose, Ebru; Karakose, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2021)
Drones are used in many areas, from military fields to the medical sector, from search and rescue activities to delivery of cargo packages. The usage areas of drones are many and they are increasing day by day. Therefore, in order to determine the routes to be used by the drones, some optimization studies such as route optimizations, optimization of the battery and the load it carries, and improvement of usage safety are required. In this study, QR code generation and QR code reading modules were created in order to improve the delivery of the order to the right user while multi-package delivery is made by drone. In addition, an optimization study was carried out on the use of the traveling salesman algorithm in order to optimize the package delivery route. Name, surname, phone and address information was requested from each user through the application. With this information, a special QR code was created for each user and sent via the application. The route was created using the traveling salesman algorithm according to the address information. The method was tested for different routes and the outputs of the method were given in the experimental results. © 2021 IEEE.
2021 International Conference on Data Analytics for Business and Industry, ICDABI 2021 -- 25 October 2021 through 26 October 2021 -- Virtual, Online -- 176070
Keywords: Drone; Multi-package delivery; QR code generation and reading; Route optimization